[99mTc]Technetium and Rhenium Dithiocarbazate Complexes: Chemical Synthesis and Biological Assessment - André Gustavo de Araujo Fernandes; Alyne Eloise Lafratta; Carolina Portela Luz; Debora Levy; Daniele de Paula Faria; Carlos Alberto Buchpiguel; Ulrich Abram; Victor Marcelo Deflon; Fabio Luiz Navarro Marques (Pharmaceutics)
Background/Objectives: Dithiocarbazates (DTCs) and their metal complexes have been studied regarding their property as anticancer activities. In this work, using S-benzyl-5-hydroxy-3-methyl-5-phenyl-4,5-dihydro-1H-pirazol-1-carbodithionate (H2bdtc), we prepared [ReO(bdtc)(Hbdtc)] and [[99mTc]TcO(bdtc)(Hbdtc)] complexes for tumor uptake and animal biodistribution studies. Methods: Re complex was prepared by a reaction of H2bdtc and (NBu4)[ReOCl4], the final product was characterized by IR, 1H NMR, CHN, and MS-ESI. 99mTc complex was prepared by the reaction of H2bdtc and [[99mTc]TcO4− and analyzed by planar and HPLC radiochromatography, and the stability was evaluated against amino acids and plasma. Biodistribution was performed in C57B/6 mice with B16F10 and TM1M implanted tumor. Results: Re is asymmetric coordinated by two dithiocarbazate ligands, one with O,N,S chelation, and the other with N,S chelation; [[99mTc]TcO(bdtc)(Hbdtc)] was prepared with a radiochemical yield of around 93%. The radioactive complex is hydrophobic (LogP = 1.03), stable for 6 h in PBS and L-histidine solution; stable for 1 h in plasma, but unstable in the presence of L-cysteine. Ex vivo biodistribution demonstrated that the compound has a fast and persistent (until 2 h) uptake by the spleen (55.46%), and tumor B16F10 and TM1M uptake is lower than 1%. In vivo SPECT/CT imaging confirmed ex vivo biodistribution, except by heterogenous TM1M accumulation but not in the B16-F10 lineage. Conclusions: H2bdtc proved to be an interesting chelator for rhenium or [99mTc]technetium. The right spleen uptake opened the opportunity to deepen the study of the molecule in this tissue and justifies future studies to identify the reason of heterogenous uptake in TM1M tumor uptake.